The Distribution and Elimination of Lufenuron in Atlantic Salmon (Salmo salar) - Røiom, Astrid Therese (The University of Bergen, 2024)
Salmon lice (Lepeophtheirus salmonis) are a growing problem in the Norwegian aquaculture industry with an estimated annual cost of sea lice management of 525 million USD in 2019 in Norway. Numerous lice treatments exist, yet chemical methods falter as lice increasingly resist today’s commonly used pharmaceuticals. Therefore, it is of interest to investigate new potential pharmaceuticals that can be used as chemical treatments in Norway. One of these potential pharmaceuticals is lufenuron, a benzoylurea, that is already used as a salmon lice treatment in some countries, such as Chile. The purpose of this thesis was to determine the levels of lufenuron in different tissue types in Atlantic salmon (Salmo salar) over time and from this data determine several pharmacokinetic parameters of lufenuron in Atlantic salmon. Understanding lufenuron’s pharmacokinetics is crucial, given its novelty as a salmon delousing agent and the current scarcity of comprehensive information. The concentration of lufenuron in the salmon tissue samples was determined using LC-MS/MS. The results showed that the concentration of lufenuron was highest in the skin and liver, while plasma had the lowest concentrations of lufenuron. The results also indicated that plasma is the main route of elimination, and the bile is the main excretory pathway for lufenuron in Atlantic salmon. In addition, the calculated half-lives of lufenuron in the different matrices suggested that lufenuron is very persistent in the tissues of Atlantic salmon compared to other veterinary drugs. Masteroppgave i kjemi KJEM399 MAMN-KJEM